(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Formulation of the problem. The production of high-quality, environmentally friendly green beans is possible through the implementation of biological technology, which involves enhancing the functioning of the symbiotic system by applying bacterial fertilizers based on highly effective strains of rhizobia. Physiologically active substances of natural origin and chelated forms of micronutrients play a significant role in determining bean yield. Such components found in the latest biological products advertised by many of their manufacturers. For example, the “Organica” brand recommends using biological products such as Azotix and Potassium Humate for pre-sowing seed treatment and Mega Harvest for foliar feeding to increase bean yield. Research materials and methods. Field studies on the effect of pre-sowing seed treatment and foliar application of biological products on the growth and yield of the Panna bean variety were conducted in 2023–2025 at the university’s experimental field. The soil was typical heavy loamy chernozem on carbonate loess. The experimental design included the following pre-sowing seed treatment options: 1. Control (dry seeds), 2. Water, 3. Potassium humate, 4. Azotix, 5. Azotix + Potassium humate, 6. Azotix + Potassium humate + a single foliar application of Mega Harvest, 7. Azotix + Potassium humate + two foliar applications of Mega Harvest. Total plot area – 10 m², recorded area – 6 m². Research results. This article presents the results of a three-year study examining the effect of pre-sowing seed treatment with the biological products Azotix and Potassium Humate, as well as foliar application of the biofertilizer Mega Harvest, on the growth and yield of the Panna bean variety. It was found that the applied biological preparations had a positive effect on plant density, survival rate, and biometric, symbiotic, and photosynthetic indicators. Among the experimental treatments, the lowest values were observed in the control, while the highest were observed with pre-sowing seed treatment using a mixture of the aforementioned biological preparations followed by foliar feeding of the plants during the branching and budding stages with the biofertilizer Mega Harvest. In 2023, the grain yield of beans across the experimental treatments ranged from 2.02 to 2.40 t/ha. In 2024, it was very low—0.42–0.62 t/ha—and in 2025, although it increased compared to the previous year, it was still low—ranging from 0.95 to 1.21 t/ha. On average over the three years of research, the grain yield of the Panna bean variety across the experimental treatments ranged from 1.13 to 1.41 t/ha, with the lowest yield in the control and the highest when using Azotix and potassium humate for pre-sowing seed treatment and two applications of the Mega Harvest biofertilizer. This treatment yielded the highest yield increase—0.28 t/ha or 24.8% compared to the control. Conclusions. The use of a combined pre-sowing seed treatment with biological products from the “Organica” brand—Azotix and Potassium Humate—followed by two applications of the Mega Harvest biofertilizer in the cultivation of the Panna bean variety has a positive effect on growth processes and yield formation, even under extreme weather conditions. Three-year studies indicate that the use of biological products contributed to increased plant density and survival rates. The lowest values were recorded in the control group, while the highest were observed with pre-sowing seed treatment using a mixture of Azotix and Potassium Humate, followed by two applications of the Mega Harvest biofertilizer. The applied biological products also had a positive effect on the plants’ biometric, symbiotic, photosynthetic, and structural indicators.